2016
DOI: 10.1007/s00276-016-1771-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of frontal hairline patterns for natural design and restoration

Abstract: Ideal reconstruction of scalp defects relies on a comprehensive understanding of scalp anatomy and detailed information of patient factors. The classification of the hairline and measured forehead reference lengths will be beneficial in the correction of wide foreheads. There were significant gender differences in the esthetic rankings of the hairline contour. Compared to women, both of the measured average forehead reference lengths displayed a significantly greater value in men. Our results clearly showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
2
28
2
Order By: Relevance
“…Spiegel in 2011 reported only a 1.8% complication rate for scalp advancement with frontal cranioplasty and brow lift, and these complications were most typically widened scar . The average height for a forehead in women (trichion to glabella) is 55 mm ± 5 mm and in men 60 mm ± 10 mm . We were on average able to advance the hairline 2.01 cm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Spiegel in 2011 reported only a 1.8% complication rate for scalp advancement with frontal cranioplasty and brow lift, and these complications were most typically widened scar . The average height for a forehead in women (trichion to glabella) is 55 mm ± 5 mm and in men 60 mm ± 10 mm . We were on average able to advance the hairline 2.01 cm.…”
Section: Discussionmentioning
confidence: 97%
“…An M‐type line is more masculine, and a rounder hairline is preferred for women . The M‐type hairline also was less attractive and made the face appear larger . In the study by Sirinturk et al, they found that the round and rectangular hairline types were mainly found in women and the M‐shape hairline was found more commonly in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020; 30(1):e92710. Standardization with the Frankfort horizontal plane is achieved in many studies with craniofacial anthropometric measurements (3,4,17). In profile view, Frankfort horizontal plane is the line connecting the highest point of the opening of the external auditory canal and the lowest Iran J Pediatr.…”
Section: Discussionmentioning
confidence: 99%
“…Since craniofacial anthropometry and morphometric measurements are affected by genetic, embryogenic and environmental factors, these measurements are used in determination of variations and medical problems associated with the development (7,(10)(11)(12)(13)(14)(15)(16)(17). Although growth retardation is a well-known, common finding in children with celiac disease, the extent to which craniofacial development is affected is not known clearly (16).…”
Section: Introductionmentioning
confidence: 99%